The man who married the moon. - Lummis, Charles Fletcher, 1859-1928 (Digital Scanning, 2001)
The Man Who Married The Moon is a collection of Pueblo Indian folk stories by renowned southwestern author, librarian, historian and archeologist Charles F. Lummis. Born in Lynn, Massachusetts and a graduate of Harvard University, Lummis moved to New Mexico because of lung disease. There he lived for five years in the quaint village of Isleta, the chief city of the Tee-Wahn tribe (spelled Tigua by Spanish authors), located in the southernmost part of the Pueblo lands, in what is now New Mexico.